2016
DOI: 10.1016/j.jmmm.2015.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Study of paramagnetic defect centers in as-grown and annealed TiO 2 anatase and rutile nanoparticles by a variable-temperature X-band and high-frequency (236 GHz) EPR

Abstract: Detailed EPR investigations on as-grown and annealed TiO2 nanoparticles in the anatase and rutile phases were carried out at X-band (9.6 GHz) at 77, 120–300 K and at 236 GHz at 292 K. The analysis of EPR data for as-grown and annealed anatase and rutile samples revealed the presence of several paramagnetic centers: Ti3+, O−, adsorbed oxygen (O2−) and oxygen vacancies. On the other hand, in as-grown rutile samples, there were observed EPR lines due to adsorbed oxygen (O2−) and the Fe3+ ions in both Ti4+ substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…According to Table 1, anatase phase and rutile phase have the same crystal system which was tetragonal but different in space group. During the conversion from space group I41/amd to P42/mnm, it can be said to be a phenomena of reconstructive polymorphism which caused by reassembly of atoms and extensive rearrangement of atomic bonds [7]. According to kais and Misra [7,8], anatase structure can be converted into rutile structure by annealing from 600 °C and completed at 1000 °C.…”
Section: Crystallography Of Calcined Tio2mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Table 1, anatase phase and rutile phase have the same crystal system which was tetragonal but different in space group. During the conversion from space group I41/amd to P42/mnm, it can be said to be a phenomena of reconstructive polymorphism which caused by reassembly of atoms and extensive rearrangement of atomic bonds [7]. According to kais and Misra [7,8], anatase structure can be converted into rutile structure by annealing from 600 °C and completed at 1000 °C.…”
Section: Crystallography Of Calcined Tio2mentioning
confidence: 99%
“…The phase transition of TiO2 from anatase phase to rutile phase, a symmetry change from I41/amd to P42/mnm due to low stability of low density solid phase of anatase. Kais and Misra studied that the conversion from anatase structure to rutile structure can be done by annealing at temperature 600 °C and completed at 1000 °C [7,8]. However, Su et al [1], Papoulis et al [9] and Wang et al [10] found that small fraction of rutile mixed with anatase had shown excellent photocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the photocatalytic technology has been utilized in numerous applications, including deodorization, bacterial and viral disinfection, and air and water decontamination [8][9][10][11]. The technology is also easy to implement as it essentially requires an ultraviolet light source and a photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The sheet resistivity values of anatase, rutile and TiO2(300) are 1.3 ×10 10 Ω square -1 , 2.6 ×10 10 Ω square -1 and 2.4 ×10 7 Ω square -1 , indicating a high electron conductivity of TiO2(300) compared to the pure anatase and rutile. More oxygen vacancies prefer to form in the anatase than rutile 45 and form a shallow donor in anatase 46 , as depicted in the Figure 2e, implying a facile electron conduction in the anatase component. Annealing of the hydrothermally-obtained TiO2 at 500 o C, TiO2(500), enhances the EPR signal compared to TiO2(300) because the annealing of anatase and rutile in the air can increase the population of oxygen vacancies in both phases and adsorbed oxygen (O2 -) in rutile 45 .…”
Section: Resultsmentioning
confidence: 93%